Seismic resistance assessment of a diverting rock-earth dam heightened with tailings dam - Ljupcho Petkovski, Stevcho Mitovski (Greek Committee On Large Dams (GCOLD), 2024)
The need to provide an additional volume for depositing tailings material, necessary for the regular operation of mines in conditions of spatial limitation, actualizes the heightening of the tailings storage facilities. The upgrade of the existing tailings storage facilities, with the upstream construction method of a new tailing sandy dams over the existing waste lagoon, is a heterogenic geo environment that is susceptible to liquefaction during dynamic (cyclic) loading and therefore they are the civil engineering structures with the highest stability risk. This heightening is characterized by detailed geotechnical in-situ investigations, sophisticated structural analyses (static, non-steady seepage, and dynamic), and necessary modification of the geometry of the embankment. That is illustrated by the results of the dynamic analysis and seismic resistance assessment of a heightening of the existing upstream combined diverting dam and modification of the previous rockfill dam with clay core, with tailings sandy dam above the waste lagoon of the tailings storage facility Toranica, Kriva Palanka, Republic of North Macedonia.
Keywords: Tailings dam, Heightening, Seismic resistance